Food consumption markers and minimum dietary diversity in different complementary feeding methods: a randomized clinical trial - Paula Ruffoni Moreira; Leandro Meirelles Nunes; Bruna Oliveira de Vargas; Erissandra Gomes; Juliana Rombaldi Bernardi (Universidade do Estado do Rio de Janeiro, 2023)
Objective: To evaluate food consumption markers and minimum dietary diversity in 12-month-old infants exposed to different methods of food introduction. Methods: A randomized clinical trial with mother-infant pairs undergoing intervention on food introduction in three methods: Parent-Led Weaning (PLW), Baby-Led Introduction to SolidS (BLISS), and mixed (combination of the two techniques). Food consumption markers were evaluated by an online questionnaire at 12 months based on food consumed the previous day, using food consumption markers for children under 2 years of the Food and Nutrition Surveillance System. The study was approved by the ethics committee. Results: At 12 months, 136 children were evaluated: 45 allocated to PLW, 48 to BLISS, and 43 to mixed. The foods with the highest prevalence of consumption were breast milk 103 (75.7%), vegetables 122 (89.7%), meat 135 (99.3%), beans 115 (84.6%), rice, potatoes, or yam 135 (99.3%). Ultra-processed foods were present in the diet of infants, including hamburgers or sausages 3 (2.2%), sweetened beverages 2 (1.5%), instant noodles 4 (2.9%), and sandwich cookies 2 (1.5 %). No differences were found between the methods of introducing complementary feeding. The minimum dietary diversity was present in the diet of 22 infants (16.2%), being: 6 (13.3%) in the PLW, 8 (16.7%) in the BLISS, and 8 (18.6%) in the mixed (p=0.793). Conclusion: Breast milk, vegetables, meat, beans, and rice were present in the diet of most infants; however, the prevalence of minimal dietary diversity was low. The consumption of ultra-processed foods was also present in the diet of infants.   Brazilian Registry of Clinical Trials (ReBEC) identification RBR-229scm.